2005
DOI: 10.1111/j.1477-9552.2005.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Differentiated Trade and Differences in Factor Endowment: The Case of Agri-Food Products between Hungary and the EU

Abstract: The paper investigates the relationship between factor endowment and vertical intraindustry trade (IIT)in agri‐food products between Hungary and the EU. Intra‐industry trade is separated into its horizontal and vertical components on the basis of differences in unit values. Three different approaches to measuring IIT are employed and these are then tested using panel regression models. Results show vertical type trade is predominant in total IIT for agri‐food products. In order to achieve more general results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 35 publications
6
17
2
Order By: Relevance
“…Our fi ndings are similar to the majority of the literature (Fertő, 2005;Turkcan and Ates, 2010;Jámbor, 2014) who found a negative relationship between vertical IIT and GDP per capita differences. Similarly to studies on manufacturing sectors, the results do not support comparative advantage explanation of vertical IIT (Milgram-Baleix and MoroEgido, 2010).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Our fi ndings are similar to the majority of the literature (Fertő, 2005;Turkcan and Ates, 2010;Jámbor, 2014) who found a negative relationship between vertical IIT and GDP per capita differences. Similarly to studies on manufacturing sectors, the results do not support comparative advantage explanation of vertical IIT (Milgram-Baleix and MoroEgido, 2010).…”
Section: Resultssupporting
confidence: 81%
“…However, low values for total IIT (the sum of vertical and horizontal IIT) suggest that IIT prevails in the agri-food trade of these countries with the EU in the analysed period. These fi ndings are consistent with the results of previous research (Fertő, 2005;Jámbor, 2014) and with earlier studies indicating that proportion of the IIT was higher for food products involving a greater degree of processing (McCorriston and Sheldon, 1991;Qasmi and Fausti, 2001). …”
Section: The Nature Of Intra-industry Trade In the Visegrad Countriessupporting
confidence: 83%
See 2 more Smart Citations
“…They also emphasised that difference between countries in relative factor endowments lead to more inter-industry trade, which in turn suppresses IIT and vertical IIT. Fertô (2005Fertô ( , 2007 analysed Hungarian intra-industry agri-food trade patterns with the EU15 and confirmed the comparative advantage explanation of vertical IIT, while stressing that using a measure of IIT that reflects the level of trade produces better regression results than those based on the degree or share of IIT. Caetano and Galego (2007) were searching for the determinants of intra-industry trade within an enlarged Europe and found that determinants of horizontal and vertical IIT differed, although both had a statistically significant relationship with a country's size and foreign direct investment.…”
Section: Literature Reviewmentioning
confidence: 99%